Experiences of Women Who Have Had Carrier Testing for Duchenne Muscular Dystrophy and Becker Muscular Dystrophy During Adolescence - Fraser, Harry G. (J Genet Couns, 2018)
Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are X-linked recessive degenerative muscular conditions. Carrier testing is available to at-risk females. Though carrier testing is often offered to adolescent females, it raises ethical issues related to autonomy. This study aimed to address the impact of DMD/BMD carrier testing during adolescence, to elucidate what motivates adolescents to seek testing, and to assess the carrier testing experience. Retrospective semi-structured telephone interviews were conducted with 12 women out of 28 initially contacted. Data were coded using thematic analysis. For most (8/12) participants, discovering their carrier status during adolescence appeared to have helped alleviate uncertainty. The majority (9/12) of participants felt that they had made an autonomous decision and most (10/12) seemed to have adjusted well to their test result. Reproductive factors were framed as having been a key motivator prior to testing. However, following testing, participants’ views on prenatal diagnosis seemed more closely linked to their lived experience than to their test result. Just over half (7/12) the participants reported having not had the opportunity for genetic counseling prior to testing and after receiving their result, an issue that warrants further consideration. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10897-018-0266-0) contains supplementary material, which is available to authorized users.